Post-marketing risk analysis of bendamustine: a real-world approach based on the FAERS database - Dan Li; Yuan Zhang; Jia Qi Ni; Jia Qi Ni; Jia Qi Ni; Juan Zhu; Wen Ting Lu; Ya Lin Chen; Lei Cheng; Yu Qi Wang; Qian Jiang Li; Jie Wang; et al. (Frontiers Media S.A., 2024)
Objective: Bendamustine was approved for treating chronic lymphocytic leukemia and indolent B-cell non-Hodgkin lymphoma. Despite its therapeutic benefits, the long-term safety of bendamustine in a large population remains inadequately understood. This study evaluates the adverse events (AEs) associated with bendamustine, using a real-world pharmacovigilance database to support its clinical application.Methods: We conducted a post-marketing risk analysis to assess the association between bendamustine and its AEs. Data were extracted from the US FDA's Adverse Event Reporting System (FAERS), covering the period from January 2017 to September 2023. The characteristics of bendamustine-associated AEs and the onset time were further analyzed. Statistical analysis was performed using MYSQL 8.0, Navicat Premium 15, Microsoft EXCEL 2016, and Minitab 21.0.Results: 9,461,874 reports were collected from the FAERS database, 9,131 identified bendamustine as the "primary suspected" drug. We identified 331 significant disproportionality preferred terms (PTs). Common AEs included pyrexia, neutropenia, infusion site reaction, progressive multifocal leukoencephalopathy (PML), injection site vasculitis, and pneumonia-all documented on bendamustine's label. Notably, 16 unexpected and significant AEs were discovered, including hypogammaglobulinemia, which is concerning due to its potential to increase infection susceptibility following bendamustine treatment. Other significant findings were anaphylactic reactions, PML, and cutaneous malignancies, suggesting updates to the drug's label may be necessary. Physicians should monitor for neurological and skin changes in patients and discontinue treatment if PML is suspected. Moreover, the median onset time for bendamustine-associated AEs was 13 days, with an interquartile range [IQR] of 0-59 days, predominantly occurring on the first day post-initiation. The β of bendamustine-related AEs suggested risk reduction over time.Conclusion: Our study uncovered some potential pharmacovigilance signals for bendamustine, providing important insights for its safe and effective clinical use.